PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Melati Melati; Laura Natasya Saragih; Audry Hafifa Listy Biran; Ade Rizky Syuhada; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to assess the impact of Good Corporate Governance (GCG) implementation on company value. GCG is a vital structure for enhancing investor confidence and creating a sustainable business environment. The methods used in this study are literature review and case analysis, with the Wilmar Group as an example of initiating GCG practices and their impact on company value. The analysis results show that proper implementation of GCG principles can enhance investor confidence, improve company reputation, and positively contribute to increasing company value. Conversely, violations of GCG principles can lead to reputational risks, financial losses, and a decline in company value.